2007
DOI: 10.3171/ped-07/10/275
|View full text |Cite
|
Sign up to set email alerts
|

Seizure freedom after functional hemispherectomy and a possible role for the insular cortex: the Dutch experience

Abstract: In this group of Dutch pediatric and adolescent patients, residual insular cortex was positively correlated with persistent postoperative seizures. Given the small sample size in this study, however, caution should be used in drawing conclusions about the role of the insular cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 27 publications
0
34
0
6
Order By: Relevance
“…20,21 We found that patients with Sturge-Weber syndrome, Rasmussen encephalitis, and focal infarct pathologies had excellent seizure control after hemispherectomy. However, patients with cortical dysplasia and hemimegalenencephaly appeared to derive benefit from PIH rather than HD, suggesting that surgical technique may play a role in seizure-control rates.…”
Section: Discussionmentioning
confidence: 97%
“…20,21 We found that patients with Sturge-Weber syndrome, Rasmussen encephalitis, and focal infarct pathologies had excellent seizure control after hemispherectomy. However, patients with cortical dysplasia and hemimegalenencephaly appeared to derive benefit from PIH rather than HD, suggesting that surgical technique may play a role in seizure-control rates.…”
Section: Discussionmentioning
confidence: 97%
“…Again, Rasmussen and Sturge-Weber syndromes and vascular insults had a better prognosis (94.6% of patients became seizure free) than did multilobar cerebral dysplasia and other etiologies (68% seizure free). 9,10,18,21,22,34,36,55,60,65 When comparing different techniques, the seizure outcome seems to be constant. Another case series comparing anatomical hemispherectomy, functional hemispherectomy, and hemispherotomy 12 showed no significant differences between the 3 groups, with 71% of patients overall…”
Section: Surgical Outcomementioning
confidence: 99%
“…В некоторых сериях опи-сываются больные, которых оперировали повторно из-за продолжающихся припадков с хорошим исхо-дом [21]. Обсуждается также роль коры островка в эпилептогенезе [22]. Типичной зоной, в которой часть проводящих путей находят сохранными, явля-ется основание лобной доли.…”
Section: Discussionunclassified
“…В этой связи при латераль-ных вариантах гемисферотомии ряд хирургов [22] считают целесообразным дополнять деафферента-цию гемисферы резекцией островка. Мы не всегда прибегали к этому приему и, следуя рекомендациям J. Schramm [8], использовали его лишь у некоторых детей с энцефалитом Расмуссена и полимикрогири-ей (см.…”
Section: Discussionunclassified